Tessituras entre coordenadores pedagógicos e professores em contexto de formação: em foco, o processo formativo do CP - Souza, Regina Garcia Toledo de (2021)
This thesis focused on the continuous training process developed by the researcher, in 2019, at the request of a recently nominated Pedagogical Coordinator (CP). Joined by three other CPs, from three different schools of the Public Education System of the state of São Paulo, they became the participants of this research. Its main objective was to analyse training necessities expressed by the four CPs in training their teachers, and which aspects of their training process were considered more significant to address those necessities. Specific objectives were: (a) to know and to analyse the course of participants’ training for coordination; (b) to identify expectations and necessities of the participants towards teachers’ training; (c) to identify and analyse what the CPs think about their attributions; (d) to map their perceptions about the school context through diagnostic assessment; (e) to identify emotions and feelings that fundament their interpersonal relationships during the developed training process. These objectives were guided by the intent (f) to allow self-assessment and, therefore, the possibility of restructuring the participants professional practices. Qualitative approach was chosen for this research. Theoretical base is supported by the “The Pedagogical Coordinator” collection (Coleção “O Coordenador Pedagógico”), published between 1998 and 2021; the theory of types of knowledge by Tardif (1991; 2014); the reconstruction of the practice by Canário (1998) and training focused on the trainer by Imbernón (2009; 2011; 2016), as well as the contributions of Henri Wallon (1975a; 1975b; 1979; 1986a; 1986b; 1995; 2007) for the CP work, which claims the importance of functional integration, and interpersonal relationships at schools, based on the studies of Almeida (2012; 2014), Mahoney & Almeida (2000; 2004; 2005) and Prandini (2004). As to methodological steps, we proposed diagnostic assessment using the following procedures: brief analysis of school documents; a questionnaire answered by over 100 teachers participating of ATPCs, five yarning circles with teachers of each of the three (15 in total), promoted during ATPCs, about the topics discussed at the questionnaires. Data was produced by reflexive interviews (SZYMANSKI, ALMEIDA & PRANDINI, 2018) at the end of the training process. We also considered data generated in meetings or in informal conversation with the participants through communication apps. Results revealed that training meetings are privileged moments that provided exchange of knowledge, especially to CPs. The thesis defended, that CPs feel insecure to conduct training processes with their teachers because they haven’t received proper training; that they acknowledge their training roles; and that they attempt to improve themselves as trainers on their own accounts, was confirmed